Synthesis of New A-CD Estrogenic Compounds: D-Homo-analogs Lacking B-ring - Dadgar, Armin; Shafiee, Abbas; Navidpour, Latifeh (Current Organic Chemistry, 2016)
Prolonged exposure to estrogens as hormone replacement therapy agents to relieve menopausal symptoms is linked to an increased risk of breast and other types of human cancers. Previous studies showed the carcinogenic effect of estrogens occurred through formation of carcinogenic/tumor initiating quinone metabolites. Hence, it was found that occupying both ortho-positions by substituents on the A-ring effectively prevent the quinone formation. Hence, a new substituted phenolic series of A-CD estrogen family, where the five-membered Dring is substituted with a six-membered one, was designed and synthesized. Desired compounds were prepared by stereospecific reduction of Wieland-Miescher ketone followed by coupling with lithiated protected phenols. Dehydration of corresponding alcohols afforded the alkene intermediates. Final hydrogenation removed the protecting group and selectively reduced the double bond to give the desired 9-(S)-isomer.
Keywords: wieland-miescher ketone